Colonic Metastases from Pleomorphic Carcinoma of the Lung Presenting as an Ileocecal Intussusception - Rashid, Sadat (International Scholarly Research Network, 2011)
Pleomorphic carcinoma is a rare aggressive type of lung cancer that uncommonly metastasizes to the bowel, leading to bleeding, perforation, obstruction, and rarely intussusception. Serving as a lead point, metastatic lesions in the bowel may precipitate intussusception and require immediate surgical intervention. We present a rare case of colonic metastases from a primary lung malignancy, causing ileocecal intussusception in a 57-year old male.